Licitaç\~oes, contratos e mercado de trabalho no Brasil - André Gambier Campos (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– The main question of this paper is whether the bids and contracts undertaken by the State could collaborate with the public-regulation of the labor market in Brazil. The present moment is conducive to the formulation of this question because there is a bill in National Congress proposing amendments to Law no 8.666/1993, which is the general statute of bidding and public contracting. This paper assesses the possibilities for using the bidding and public contracting to regulate the labor market, from three different perspectives, involving: i) only the bidding companies; ii) also its suppliers of inputs; iii) institutions which control the operation of all these companies and also the functioning of the labor market as a whole. Simultaneously, this paper assesses these possibilities from two complementary moments, involving: i) only the bids (where you pick companies that will contract with the state); ii) involving also the implementation of public contracts.
Keywords: J08; J80; H83; 330